ANALISIS EGO STATE DALAM PROSES KONSELING INDIVIDUAL PADA GURU BIMBINGAN DAN KONSELING - Sri Laelatul Pazriah; Rini Susanti Minarso (Bimbingan dan Konseling, FKIP, Universitas Nahdlatul Ulama Cirebon, 2019)
This study is an analysis of ego state that often arises when individual counseling is carried out by the counselor. The ego state referred to in this study includes the ego state Parent, Adult and Child. This study is a qualitative study using the content analysis method. The results of this study are that the ego state that appears during individual counseling is the Ego State Parent on word indicators while for other indicators such as Intonation, gestures, posture and more facial expressions on the ego state Adult.